Impact of high oxygen and vacuum retail ready packaging formats on lamb loin and topside eating quality. (January 2017) - Frank, Damian Conrad; Geesink, Geert; Alvarenga, Tharcilla I.R.C.; Polkinghorne, Rod; Stark, Janet; Lee, Michael; Warner, Robyn
Abstract: Lamb steaks from semimembranosus (SM) and longissimus thoracis et lumborum (LTL) muscles were allocated to three different packaging treatments — Darfresh® vacuum skin packaging (VSP), Darfresh® Bloom packaging (80% O2 :20% CO2 ; Hi-Ox-DB) or high oxygen modified atmosphere packaging (80% O2 :20% CO2 ; Hi-Ox-MAP) — and stored in simulated retail display for 5 or 10 days and then subjected to consumer sensory and chemical analyses. Hi-Ox-MAP and Hi-Ox-DB samples had lower tenderness, flavor, juiciness and overall liking scores and higher TBARS values, compared to VSP. Hi-Ox-MAP samples deteriorated in juiciness and flavor between 5 and 10 days. Hi-Ox-MAP LTL samples had a lower myofibrillar fragmentation index, consistent with reduced proteolysis, although desmin proteolysis and desmin and troponin-T cross-linking were not influenced by packaging. The LTL exhibited greater desmin degradation and reduced desmin cross-linking relative to the SM, supporting the higher tenderness scores in this muscle. Direct packaging of lamb into retail ready VSP may provide the sheepmeat industry with greater flexibility while increasing consumer satisfaction.